Experimental assessment of tundra fire impact on element export and storage in permafrost peatlands - Kuzmina, Daria M.; Lim, Artem G.; Loiko, Sergey V.; Pokrovsky, Oleg S. (Science of The Total Environment, 2022)
Extensive studies have been performed on wildfire impact on terrestrial and aquatic ecosystems in the taiga biome, however consequences of wildfires in the tundra biome remain poorly understood. In such a biome, permafrost peatlands occupy a sizable territory in the Northern Hemisphere and present an extensive and highly vulnerable storage of organic carbon. Here we used an experimental approach to model the impact of ash produced from burning of main tundra organic constituents (i.e., moss, lichen and peat) on surrounding aquatic ecosystems. We studied the chemical composition of aqueous leachates produced during short-term (1 week) interaction of ash with distilled water and organic-rich lake water at 5 gsolid L−1 and 20 °C. The addition of ash enriched the fluid phase in major cations (i.e., Na, Ca, Mg), macro- (i.e., P, K, Si) and micronutrients (i.e., Mn, Fe, Co, Ni, Zn, Mo). This enrichment occurred over <2 days of experiment. Among 3 studied substrates, moss ash released the largest amount of macro- and microcomponents into the aqueous solution. To place the obtained results in the environmental context of a peatbog watershed, we assume a fire return interval of 56 years and that the entire 0–10 cm of upper peat is subjected to fire impact. These mass balance calculations demonstrated that maximal possible delivery of elements from ash after soil burning to the hydrological network is negligibly small (<1–2 %) compared to the annual riverine export flux and element storage in thermokarst lakes. As such, even a 5–10 fold increase in tundra wildfire frequency may not sizably modify nutrient and metal fluxes and pools in the surrounding aquatic ecosystems. This result requires revisiting the current paradigm on the importance of wildfire impact on permafrost peatlands and calls a need for experimental work on other ecosystem compartments (litter, shrubs, frozen peat) which are subjected to fire events.